Minutes of the CCAFS 10th Independent Steering Committee Meeting, 10-11 November 2021 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
10th INDEPENDENT STEERING COMMITTEE MEETING